Evolution of hydrocarbon deposits in the South Caspian Basin - Seidov, V.M.; Khalilova, L.N. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2023)
Studies of the South Caspian Basin display that the Early Pliocene sediments define mainly the structural characteristic of the section in this area. The Productive Series consists of deposits accumulated during the Pliocene epoch. It is known that within the basin, the major commercial hydrocarbon accumulations are attributed to the Productive Series of the Early Pliocene and concentrated mainly in the Absheron oil and gas province, Baku archipelago and Low Kur oil and gas provinces. Studies of fluid generation are required for correct planning of geological exploration for oil and gas in these areas. This research work aimed to study the fluid generation processes in the South Caspian Basin by use of 3D modeling. The history of hydrocarbon formation was reconstructed. Fluid generation focuses were studied and the distribution areas of these focuses was clarified. The maturity of the Middle Jurassic and Low Cretaceous sediments and Maikop and Diatom deposits were assessed, the temperature regime of the Maikop and Diatom deposits were analyzed. We also evaluated the hydrocarbon fields’ and mud volcanoes’ relations to the focal areas of small-focused earthquakes. In the South Caspian Basin, the Middle Jurassic, Low Cretaceous, Maykop, and Diatom focuses of fluid generation were outlined and their allocation and time-spatial evolution history were researched. Evaluation of the maturity of Middle Jurassic and Low Cretaceous sediments, Maykop, and Diatom showed neither oil formed at the peak of oil-gas generation with maturity values Ro=0.8ﬀ0.9 %, nor low-maturity gases of the transition zone even within the fluids of gas-condensate fields, while some oil fields had gases of abnormally high maturity of Ro=2.4ﬀ3.09 %. 3D modeling of paleogeotemperatures in Maykop and Diatom suites found that a) both in the western and the eastern part of the South Caspian Basin the temperature in the bottom of Maykop increases by 20 ◦C in comparison to the top of the suite; b) in the west of the trough in the middle portion of Diatom at a depth of 8000 m and in the east of the trough at 9000 m, the temperature reaches 120 ◦C. In the case of small-focused seismicity caused by fluid-generation processes, the latter at the phase conversions are accompanied by high energy output, decompaction, pressing-out of fluids and matters in pseudo-liquefied state into the permeable areas of the media, thus assisting the development of diapiric structures and mud volcanoes.